International trade and factor productivity as determinants of the real effective exchange rate - Dabós, Marcelo (2016)
Using large panel data models that deal with the problems of potential endogeneity and cross-sectional dependence, while also allowing for cross-country heterogeneity in the parameters of interest, we demonstrated that trade openness produces a depreciation of the real effective exchange rate and total factor productivity leads to its appreciation.